LINGUACULTURAL PERSPECTIVES ON THE CONCEPT OF "NATION" IN THE ENGLISH AND UZBEK LANGUAGES - Burieva Nilufar Gofur kizi (Bright Mind Publishing, 2025)
This paper explores the linguacultural conceptualization of the term "nation" in English and "millat" in Uzbek, highlighting how language reflects and shapes national identity, collective memory, and cultural values. Through a comparative analysis, the study examines the historical roots, semantic evolution, and pragmatic use of these terms in each language. By analyzing these terms through the lens of linguaculturology, the paper underscores how linguistic expressions of national identity are influenced by cultural narratives and historical experiences. The findings contribute to a deeper understanding of the interplay between language, culture, and identity in the context of globalization and cultural diversity.
Keywords: Linguaculturology, language, phraseology, linguistics, pragmatic function, discourse.